2014
DOI: 10.1016/j.jgo.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-based health care use correlates with incidence of adverse events among elderly Medicare patients treated in adjuvant chemotherapy trials (Alliance 70802)

Abstract: Objective Medicare claims can be useful in chemotherapy-related comparative effectiveness research (CER) estimating survival, but methods for estimating patients’ treatment morbidity are currently lacking. We sought to determine if patients’ health care use in the claims is a marker of treatment morbidity. Materials and Methods For 249 elderly Medicare patients with breast or colon cancer who were treated in two adjuvant clinical trials, we merged patients’ National Cancer Institute Common Toxicity Criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For example, our measure of patient toxicity or morbidity is hospital-based health care use. While we have previously shown that hospital-based health care use is a good proxy for chemotherapy-related toxicity among patients with colon and breast cancer treated on clinical trials, we are extrapolating those findings to patients with NSC lung cancer treated off clinical trials [26]. In addition, we studied patients living in SEER areas only; generalizability of our findings to other areas requires further study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, our measure of patient toxicity or morbidity is hospital-based health care use. While we have previously shown that hospital-based health care use is a good proxy for chemotherapy-related toxicity among patients with colon and breast cancer treated on clinical trials, we are extrapolating those findings to patients with NSC lung cancer treated off clinical trials [26]. In addition, we studied patients living in SEER areas only; generalizability of our findings to other areas requires further study.…”
Section: Discussionmentioning
confidence: 96%
“…To assess morbidity we examined health care use following initiation of chemotherapy including hospitalization, intensive care unit (ICU) stays, emergency room (ER) visits, home health, skilled nursing facility (SNF) stays, hospice and death in a hospital. The hospital-based health care that elderly Medicare patients with cancer use while they are on chemotherapy trials is strongly associated with their clinical trial measure of post-treatment morbidity [26]. Finally we examined claims for hemodialysis as cisplatin-based regimens are associated with nephrotoxicity.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…A previous Australian study reported poor agreement between chemotherapy side effects identified using administrative data compared with self-reported side effects, with the latter being significantly more common (Pearce et al, 2015). Nevertheless, hospitalisations and emergency room visits can be useful outcomes when examining different treatment options in real-world patient populations, with hospitalisations having the strongest association with a toxicity measure used in RCTs (Lamont et al, 2014). If different chemotherapy regimens are associated with only small differences in absolute efficacy, considering adverse effects becomes even more important (Ruddy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…30 We computed survival time from the first chemotherapy administration claim to date of death from the Medicare enrollment file. Follow-up was very complete, with only 68 patients (3%) censored for survival at the end of the study period.…”
Section: Variable Definitionsmentioning
confidence: 99%